1960
DOI: 10.1172/jci104106
|View full text |Cite
|
Sign up to set email alerts
|

Experience With the Chromic Oxide Method of Fecal Marking in Metabolic Balance Investigations on Humans

Abstract: In metabolic balance studies the assessment of the subject's state of balance is derived from estimates of the dietary intake and the excretion in the urine and feces of the constituent under investigation. It Many investigators employ the "time-marker" method for obtaining quantitative fecal collections giving, for instance, two doses of carmine as a marker, collecting the feces passed between the time of appearance in the feces of the first and second doses of marker, and relating this collection to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
1

Year Published

1964
1964
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(37 citation statements)
references
References 13 publications
1
34
1
1
Order By: Relevance
“…They were given a diet which was similar in content to that to which they were accustomed whilst at home. Capsules containing 33 mmol (0.5 g) of acid-washed chromium sesquioxide were given three times a day with meals as a continuous faecal marker (Whitby & Lang, 1960). Food, faeces and urine were analysed for calcium and phosphorus content.…”
Section: Methodsmentioning
confidence: 99%
“…They were given a diet which was similar in content to that to which they were accustomed whilst at home. Capsules containing 33 mmol (0.5 g) of acid-washed chromium sesquioxide were given three times a day with meals as a continuous faecal marker (Whitby & Lang, 1960). Food, faeces and urine were analysed for calcium and phosphorus content.…”
Section: Methodsmentioning
confidence: 99%
“…Chromium sesquioxide was used as a continuous faecal marker. Capsules containing 0·5 g of acid washed chromium sesquioxide were given three times a day with meals (Whitby & Lang, 1960). Carmine markers were used in all subjects at the beginning of the balance and to delineate the equilibrium period.…”
mentioning
confidence: 99%
“…Subsequent studies on humans showed that equally good intestinal mixing could be achieved if the indicator was given in capsules twice or thrice daily. 5,9 The total amount of indicator fed could be recovered from stools within 48-72 hours of the last dose.5·7"9…”
Section: Introductionmentioning
confidence: 99%
“…Analy¬ sis of stools for both indicator and test substances was made by chemical methods. 9 By using radioactive cholesterol, Stanley (1) It is not absorbed from the intestinal tract and does not have the potentially ir¬ ritant effect of chromium. Its degradation product is niobium which is also nonabsorbable and has a spectrum similar to Zr95.…”
Section: Introductionmentioning
confidence: 99%